Notch size effect on in‐phase multiaxial fatigue life prediction of steel bar specimens. Issue 3 (20th May 2019) - Song, Wei; Liu, Xuesong; Yan, Dejun
Abstract: The current paper presents a comprehensive analysis including experimental and numerical works that elucidate the effect of notch behavior on in‐phase multiaxial fatigue life. Multiaxial fatigue experiments of 45 steel and 45QT steel considering the notch radius and opening angles were performed. An investigation including analytical and computational frameworks for multiaxial fatigue analysis on the basis of average strain energy density (SED) theory was conducted to deal with the energy gradient. A bulk of new fatigue data were summarized by normal and shear stress firstly and then reanalyzed by means of the local SED by control volumes surrounding the notch tip. The notch effect on the multiaxial fatigue life is further clarified by SED theory.